2019
DOI: 10.1128/msphere.00314-19
|View full text |Cite
|
Sign up to set email alerts
|

A Heat Shock Protein 48 (HSP48) Biomolecular Condensate Is Induced during Dictyostelium discoideum Development

Abstract: The social amoeba Dictyostelium discoideum’s proteome contains a vast array of simple sequence repeats, providing a unique model to investigate proteostasis. Upon conditions of cellular stress, D. discoideum undergoes a developmental process, transitioning from a unicellular amoeba to a multicellular fruiting body. Little is known about how proteostasis is maintained during D. discoideum’s developmental process. Here, we have identified a novel α-crystallin domain-containing protein, heat shock protein 48 (HSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Such a screen could be useful for proteins that prevent processes like liquidliquid phase separation (LLPS) or promote the resolution of biomolecular condensates. This would be a useful screen as LLPS has recently been identified in Dictyostelium (Santarriaga et al, 2019). More recent work has also demonstrated that one type of biomolecular condensate, stress granules, are dynamically modulated and that different stressors alter which factors are needed to resolve the stress granules once the stressor has been removed (Gwon et al, 2021;Maxwell et al, 2021).…”
Section: Uracil Auxotrophy Can Be Utilized For Selectionmentioning
confidence: 99%
“…Such a screen could be useful for proteins that prevent processes like liquidliquid phase separation (LLPS) or promote the resolution of biomolecular condensates. This would be a useful screen as LLPS has recently been identified in Dictyostelium (Santarriaga et al, 2019). More recent work has also demonstrated that one type of biomolecular condensate, stress granules, are dynamically modulated and that different stressors alter which factors are needed to resolve the stress granules once the stressor has been removed (Gwon et al, 2021;Maxwell et al, 2021).…”
Section: Uracil Auxotrophy Can Be Utilized For Selectionmentioning
confidence: 99%